Associations of childhood bullying victimization with lifetime suicidal behaviors among new U.S. Army soldiers. Issue 8 (3rd April 2017) - Campbell‐Sills, Laura; Kessler, Ronald C.; Ursano, Robert J.; Rosellini, Anthony J.; Afifi, Tracie O.; Colpe, Lisa J.; Heeringa, Steven G.; Nock, Matthew K.; Sampson, Nancy A.; Sareen, Jitender; Schoenbaum, Michael; Sun, Xiaoying; et al.
Abstract : Background: Prior studies have documented associations of childhood bullying victimization with suicidal behaviors. However, many failed to adjust for concomitant risk factors and none investigated this relationship in military personnel. This study aimed to estimate independent associations of childhood bullying victimization with suicidal behaviors among U.S. Army soldiers. Methods: Soldiers reporting for basic training completed a cross‐sectional survey assessing mental disorders, suicidal behaviors, and childhood adversities including two types of bullying victimization: (1) Physical Assault/Theft and (2) Bullying Comments/Behaviors. Associations of childhood bullying experiences with suicidal behaviors were estimated using discrete‐time survival analysis of person–year data from 30, 436 soldiers. Models adjusted for sociodemographic factors, childhood maltreatment by adults, and mental disorders. Results: After comprehensive adjustment for other risk factors, more frequent Physical Assault/Theft by peers during childhood was associated with increased odds of lifetime suicidal ideation (adjusted odds ratio [AOR] = 1.18, 95% CI: 1.11–1.26, P < .001) and attempt (AOR = 1.30, 95% CI: 1.13‐1.50, P < .001). More frequent Bullying Comments/Behaviors were associated with increased risk of ideation (AOR = 1.30, 95% CI: 1.26‐1.35, P < .001), plan (AOR = 1.44, 95% CI: 1.35‐1.54, P < .001), attempt (AOR = 1.24, 95% CI: 1.15‐1.33, P < .001), and onset of plan among ideators (AOR = 1.09, 95% CI: 1.03‐1.15, P = .002). Relative to no bullying victimization, exposure to the most persistent bullying was associated with two‐ to fourfold increase in risk for suicidal behaviors. Conclusions: Childhood bullying victimization is associated with lifetime suicidal behaviors among new soldiers. Exposure to Bullying Comments/Behaviors during childhood is associated with progression from suicidal ideation to plan. Improved recognition of these relationships may inform risk mitigation interventions for soldiers.